Mengukur Minat Berkunjung Kembali Atas Dasar Media Sosial Dan Citra Destinasi Wisata Pantai Lon Malang Di Sampang Madura - Nuryani, Yusrianingsih; Winata, A. Yahya Surya (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study aims to determine the effect of social media on the interest in revisiting throught the image of the the destination of the Lon Malang Beach tourist destination in Sampang Madura. This research was conducted in a quantitative descriptive manner, using exploratory research, data collection techniques in the form of surveys with interviews or observations. Data analysis techniques activities are grouping data based on variables and types of respondents, metabulation, data based on variables, data presentation, performing data calculations. to test the hypothesis.The results of this study indicate that the destination image variable (X2) and social media (X1), simultaneously or together have an influence on interest in revisiting (Y) Lon Beach Malang Sampang Madura tourism. Partially the intervening variable or independent variable in this study is known that Social Media (X1) has an effect on the Image of Objective variable (X2). From the exogenous variable the destination image (X2) and social media (X1) affect the endogenous variable of interest in visiting again (Y) and from each exogenous variable it affects the endogenous variable as seen from the average respondent who answered well, where this is in accordance with the results of the analysis and proof of the hypothesis analysis, it is known that the destination image variable (X2) and social media (X1) affect the variable interest in revisiting (Y) and the social media variable (X1) affects the destination image (X2) Lon Beach Malang Sampang Madura tourism.